ANALISIS PENGARUH FRAUD DIAMOND, INTEGRITAS, DAN RELIGIUSITAS TERHADAP PERILAKU KECURANGAN AKADEMIK MAHASISWA (Studi Kasus Pada Mahasiswa Akuntansi Konsentrasi Syariah Universitas Brawijaya) - AZIZ, MUHAMMAD RUSYDI (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study examines  the factors influencing  students'  academic cheating behavior using diamond fraud concept (pressure, opportunity, rationalization and capabilities), integrity, and religiosity. This study uses a survey method to collect data. The research samples are 52 students of the Department  of Accounting  of Sharia Concentration Faculty of Economics and Business, University of Brawijaya . The results of this study indicate that the pressure and capabilities positively affect students' academic fraud behaviour. Moreover, integrity and religiosity negatively affect students' academic fraud. While the opportunity and rationalization have no effect. The implications of this study are relevant for the Accounting Department to take notice that pressure, capability, integrity, and religiosity can affect students’ academic fraud in the Department Accounting of Sharia Concentration.Keywords:  Academic  Fraud, pressure,  opportunity, rationalization,  capability, integrity, and religiosity.